Heart rate variability in schizophrenia: A comparative analysis before and after electroconvulsive therapy - Noriko Yoshida; Miho Miyajima; Yoko Suzuki; Eisuke Matsushima; Takafumi Watanabe; Rie Omoya; Mayo Fujiwara; Mitsuru Nakamura; Hidehiko Takahashi; Takashi Takeuchi (PCN Reports)
Abstract Aim The aim of this study was to investigate autonomic nervous system imbalance in schizophrenia by comparing heart rate variability (HRV) between patients with schizophrenia and healthy controls, and to assess changes in HRV in patients before and after electroconvulsive therapy (ECT). Methods HRV was compared between patients with schizophrenia (n = 17) and age‐ and gender‐matched healthy controls (n = 34). Changes in HRV were also assessed in patients pre‐ and post‐ECT. Additionally, the relationship between HRV and Positive and Negative Symptom Scale (PANSS) scores in patients with schizophrenia was investigated. Results Patients with schizophrenia showed significantly lower high‐frequency (HF) and low‐frequency (LF) power compared with healthy controls, with a trend towards a higher LF/HF ratio. Following ECT, HF power increased significantly while the LF/HF ratio decreased significantly, resulting in no significant differences between patients and controls for these HRV parameters. The associations between HRV and symptoms observed before ECT were largely diminished after ECT, with only changes in the LF component correlating with changes in PANSS scores. Conclusion Following ECT, we observed a shift in autonomic balance from sympathetic dominance towards increased parasympathetic activity and a state more closely resembling that in healthy controls.